Is the prognosis of non‐hypertensive, COVID‐19 patients treated with renin–angiotensin–aldosterone system inhibitors more uncertain?. Issue 22 (17th November 2022) - García Martínez, Juan José; Wozniak, Hannah; Salamin, Pauline; Giraud, Raphaël; Le Terrier, Christophe; Bendjelid, Karim
Abstract: Previous studies suggested that ongoing treatment with renin–angiotensin–aldosterone system (RAAS) inhibitor drugs may alter the course of SARS‐CoV‐2 infection and promote the development of more severe forms of the disease. The authors conducted a comparative, observational study to retrospectively analyze data collected from 394 patients admitted to ICU due to SARS‐CoV‐2 pneumonia. The primary aim of the study was to establish an association between the use of RAAS inhibitor drugs and mortality in the ICU. The secondary aims of the study were to establish an association between the use of RAAS inhibitor drugs and clinical severity at ICU admission, the need for tracheal intubation, total days of mechanical ventilation, and the ICU length of stay. The authors found no statistically significant difference in ICU mortality between patients on RAAS inhibitor drugs at admission and those who were not (31.3% versus 26.2% mortality, p ‐value 0.3). However, the group of patients taking RAAS inhibitor drugs appeared to be more critical at ICU admission, and this difference became statistically significant in the subgroup of non‐hypertensive patients. ICU mortality in the subgroup of non‐hypertensive patients treated with RAAS inhibitor drugs also tended to be higher. Overexpression of the angiotensin‐converting enzyme 2 (ACE2) in human cells, induced by RAAS inhibitor drugs, promotes viral entry‐replication of SARS‐CoV‐2 and alters the basal balance of the RAAS, which may explain the findings observed in the present study. These phenomena may be amplified in non‐hypertensive patients treated with RAAS inhibitor therapy. Abstract : Overexpression of the angiotensin‐converting enzyme 2 (ACE2) in human cells, induced by RAAS inhibitor drugs, promotes viral entry‐replication of SARS‐CoV‐2 and alters the basal balance of the RAAS, which may explain the more severe course of COVID‐19 suggested by the results of this study. These phenomena may be amplified in non‐hypertensive patients treated with RAAS inhibitor therapy.